Revealing Phosphorus Nitrides up to the Megabar Regime: Synthesis of α′‐P3N5, δ‐P3N5 and PN2. Issue 62 (17th October 2022) - Laniel, Dominique; Trybel, Florian; Néri, Adrien; Yin, Yuqing; Aslandukov, Andrey; Fedotenko, Timofey; Khandarkhaeva, Saiana; Tasnádi, Ferenc; Chariton, Stella; Giacobbe, Carlotta; Bright, Eleanor Lawrence; Hanfland, Michael; et al.
Abstract: Non‐metal nitrides are an exciting field of chemistry, featuring a significant number of compounds that can possess outstanding material properties. These properties mainly rely on maximizing the number of strong covalent bonds, with crosslinked XN6 octahedra frameworks being particularly attractive. In this study, the phosphorus–nitrogen system was studied up to 137 GPa in laser‐heated diamond anvil cells, and three previously unobserved phases were synthesized and characterized by single‐crystal X‐ray diffraction, Raman spectroscopy measurements and density functional theory calculations. δ‐P3 N5 and PN2 were found to form at 72 and 134 GPa, respectively, and both feature dense 3D networks of the so far elusive PN6 units. The two compounds are ultra‐incompressible, having a bulk modulus of K 0 =322 GPa for δ‐P3 N5 and 339 GPa for PN2 . Upon decompression below 7 GPa, δ‐P3 N5 undergoes a transformation into a novel α′‐P3 N5 solid, stable at ambient conditions, that has a unique structure type based on PN4 tetrahedra. The formation of α′‐P3 N5 underlines that a phase space otherwise inaccessible can be explored through materials formed under high pressure. Abstract : Phase in, phase out : Investigations of the phosphorus–nitrogen system in a laser‐heated diamond anvil cell resulted in the synthesis of new δ‐P3 N5 and PN2 phases at 72 and 134 GPa, respectively. Their structures are composed of PN6 octahedra. Upon decompression, δ‐P3 N5 transforms into the novel α′‐P3 N5 solid that is stable under ambient conditions.